Bedside detection and monitoring of pulmonary embolism using electrical impedance tomography - Deng, Mingyuan; Li, Nianze; Wang, Jiafeng; Zhao, Shuang; Yu, Mingjing (Frontiers in Physiology, 2026)
Pulmonary embolism (PE) is a common and potentially fatal obstructive disease of the pulmonary arteries; early diagnosis and continuous monitoring are particularly critical in critically ill patients. Electrical impedance tomography (EIT), a noninvasive and radiation-free imaging modality that enables real-time bedside monitoring, offers a promising approach for adjunctive diagnosis and perfusion assessment of PE, especially in patients who cannot undergo computed tomography pulmonary angiography (CTPA) due to instability or other contraindications. Building upon an overview of EIT imaging principles and recent advances in pulmonary perfusion monitoring, this review concentrates on the bedside application of EIT and the clinical value of EIT in bedside assessment of PE. Unlike prior research, this study proposes an EIT perfusion imaging strategy using a hypertonic saline bolus for the diagnosis of PE and compares it with bedside monitoring based on cardiac impedance signals. Additionally, we assess the current clinical evidence according to GRADE standards and identify its existing limitations. Finally, we further discuss the key challenges hindering clinical translation of EIT and outline future directions. This review aims to provide clinicians and researchers with a reference to facilitate broader adoption of EIT in the bedside monitoring of PE.